2006
DOI: 10.1016/s0828-282x(06)70908-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonheart failure-associated elevation of amino terminal pro-brain natriuretic peptide in the setting of sepsis

Abstract: O ne-half of a century has been spent debating the etiology of depressed myocardial function in septic shock (1). Brain natriuretic peptide (BNP) is a new biomarker for cardiac dysfunction, and most data in the literature associate its increased levels with depressed myocardial function (2-5). However, increased levels of BNP have also been found in critical illnesses associated with shock (eg, sepsis), apparently not related to myocardial dysfunction. In human myocardium, BNP is secreted in response to myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Natriuretic peptides may be useful in terms of characterizing stress on the ventricle; however, they must be interpreted with caution in the setting of ICI myocarditis as they can be elevated directly through inflammatory pathways even in the setting of normal filling pressures. 26,27 Natriuretic peptides are not specific for myocarditis but may be elevated in patients with significant left ventricular dysfunction and heart failure, and are frequently elevated in ICI-associated myocarditis. 28 In addition, natriuretic peptide elevations may be particularly complex in the setting of ICI mediated myocarditis, but the elevation may be mediated by other mechanisms such as via Interleukin-6.…”
Section: Biomarker Elevationsmentioning
confidence: 99%
“…Natriuretic peptides may be useful in terms of characterizing stress on the ventricle; however, they must be interpreted with caution in the setting of ICI myocarditis as they can be elevated directly through inflammatory pathways even in the setting of normal filling pressures. 26,27 Natriuretic peptides are not specific for myocarditis but may be elevated in patients with significant left ventricular dysfunction and heart failure, and are frequently elevated in ICI-associated myocarditis. 28 In addition, natriuretic peptide elevations may be particularly complex in the setting of ICI mediated myocarditis, but the elevation may be mediated by other mechanisms such as via Interleukin-6.…”
Section: Biomarker Elevationsmentioning
confidence: 99%
“…This relationship seems particularly important in the acute cellular cardiac allograft rejection, where inflammation plays a pivotal role [26]. Finally, another condition in which inflammation has been shown to be related with natriuretic peptide elevation independently of hemodynamics is represented by sepsis, where NT-proBNP holds a prognostic value as well [27,28].…”
Section: Inflammation As a Trigger Of Cardiac Damage And B-type Natrimentioning
confidence: 99%
“…There has also been an interest in using plasma BNP levels in patients with myocardial dysfunction related to factors other than congenital or acquired heart disease. Although previous studies in adults have suggested that BNP levels are elevated to the same extent in patients with myocardial dysfunction related to either sepsis or CHF (27,28), there are also anecdotal reports of patients with severe sepsis and elevated plasma BNP levels with normal myocardial function (29–32). The mechanisms responsible for the stimulation of the natriuretic peptide system in sepsis have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%